Practical Mobile Forensics Forensically investigate and analyze iOS, Android, and Windows 10 devices - Tamma, Rohit; Skulkin, Oleg; Mahalik, Heather; Bommisetty, Satish (Packt Publishing, 2020)
Mobile phone forensics is the science of retrieving data from a mobile phone under forensically sound conditions. This updated fourth edition of Practical Mobile Forensics delves into the concepts of mobile forensics and its importance in today's world. The book focuses on teaching you the latest forensic techniques to investigate mobile devices across various mobile platforms. You will learn forensic techniques for multiple OS versions, including iOS 11 to iOS 13, Android 8 to Android 10, and Windows 10. The book then takes you through the latest open source and commercial mobile forensic tools, enabling you to analyze and retrieve data effectively. From inspecting the device and retrieving data from the cloud, through to successfully documenting reports of your investigations, you'll explore new techniques while building on your practical knowledge. Toward the end, you will understand the reverse engineering of applications and ways to identify malware. Finally, the book guides you through parsing popular third-party applications, including Facebook and WhatsApp. By the end of this book, you will be proficient in various mobile forensic techniques to analyze and extract data from mobile devices with the help of open source solutions.